Inventory Control Analysis of Flowline Pipe (Case Study: PT. Pertamina Hulu Rokan Field Limau) - Nathasya Hevira Putri; Iwan Sukarno; Anindhita Dewabharata (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Flowline is a means of distributing oil and natural gas from drilling wells to the separation point or collection station. The need for this flowline is fast moving but the problem that often occurs in companies is that the flowline needs cannot be fulfilled. Stock out on the 4-inch flowline pipe can cause a loss of production opportunity. To overcome the stock out, it is necessary to do proper inventory control. Forecasting the demand for the 4-inch flowline pipe using the ARIMA model to determine the amount of demand in the future period. After getting the number of requests, the requests are analyzed using the ADI-CV technique to see the demand pattern. The characteristics of the demand pattern are used to determine the appropriate type of inventory control. The result of the ADI value is 1 and the CV value is 0.04, so the demand pattern is smooth moving and uses the continuous review method. The continuous review method resulted in a total cost of Rp. 17,780,325,626, while the actual cost was Rp. 18,247,993,200. These results indicate that with inventory control, the proposed condition using the continuous review method can reduce inventory costs by Rp. 467,667,574 compared to actual conditions, and there is a saving of 2.56%.